Nitinol as a suitable anode material for electricity generation in microbial fuel cells - Taskan, Ergin; Bulak, Selman; Taskan, Banu; Sasmaz, Merivan; El Abed, Soumya; El Abed, Alae (Elsevier Science Sa, 2019)
Nitinols (Nickel-titanium alloys) have a good electrical conductivity and biocompatibility with human tissue and bacteria and, therefore, can be effectively used as an anode material in bioelectrochemical systems. This paper aimed to use nitinols (at different Ni/Ti ratios) as an anode material for microbial fuel cells (MFCs) in order to achieve higher power density. The maximum power densities of the MFCs using NiTi-1, NiTi-2, and NiTi-3 electrodes were 555 mW/m2, 811 mW/m(2), and 652 mW/m(2), respectively. More bacterial adhesion was observed on the NiTi-2 electrode. Electrochemical impedance spectroscopy (EIS) results showed low charge transfer resistance at MFCs fabricated with NiTi. The biofilm observations indicate that bacterial attachment is better with NiTi-2 as compared with that on NiTi-1 and NiTi-3. The resulting mesopore and macropore rich structure significantly promote microbial colonization, enabling formation of compact electroactive biofilms with additional benefit from the excellent biocompatibility and chemical stability of NiTi-2. Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) results indicated that five groups of bacteria were the dominant phyla in the MFCs: environmental samples, b-proteobacteria, g-proteobacteria, d-proteobacteria, and CFB group bacteria. The high biocompatibility, electrical conductivity and stability of nitinols make them a more attractive anode material for MFCs. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Microbial fuel cell; Electrode; Nitinol; Biocompatibility; Porous; Molecular methods